Dimerization of Benzyl and Allyl Halides via Photoredox-Mediated Disproportionation of Organozinc Reagents - Levin, Vitalij V.; Agababyan, Daniil P.; Struchkova, Marina I.; Dilman, Alexander D. (Synthesis, 2018)
Benzyl and allyl halides undergo homocoupling when treated with zinc in the presence of a catalytic amount of a cationic iridium(III) complex under irradiation with 400 nm light-emitting diodes. The reaction proceeds through the intermediate formation of an organozinc reagent, which disproportionates to a free radical and elemental zinc under photoredox conditions.
Keywords: organozinc reagents; homocoupling; photoredox; free radicals; organic halides